2007
DOI: 10.1074/jbc.m704413200
|View full text |Cite
|
Sign up to set email alerts
|

Commonality and Biosynthesis of the O-Methyl Phosphoramidate Capsule Modification in Campylobacter jejuni

Abstract: In this study we investigated the commonality and biosynthesis of the O-methyl phosphoramidate (MeOPN) group found on the capsular polysaccharide (CPS) of Campylobacter jejuni. High resolution magic angle spinning NMR spectroscopy was used as a rapid, high throughput means to examine multiple isolates, analyze the cecal contents of colonized chickens, and screen a library of CPS mutants for the presence of MeOPN. Sixty eight percent of C. jejuni strains were found to express the MeOPN with a high prevalence am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 37 publications
(55 reference statements)
4
118
0
Order By: Relevance
“…Second, the anomeric resonance of the GalfNAc residue was very diffuse in wild type but showed a strong peak in 11168R. The GalfNAc residue is very sensitive to the surrounding modifications and will depend strongly on the presence or absence of MeOPN modifications (31). Closer examination using 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the anomeric resonance of the GalfNAc residue was very diffuse in wild type but showed a strong peak in 11168R. The GalfNAc residue is very sensitive to the surrounding modifications and will depend strongly on the presence or absence of MeOPN modifications (31). Closer examination using 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These highly conserved MeOPN biosynthesis genes have been found in about 70% of the strains sequenced to date. Similarly, McNally et al identified two distinct MeOPN transferases in NCTC 11168 responsible for addition of MeOPN to distinct sugar moieties in the NCTC 11168 CPS (23). There is variability in the predicted protein sequences of MeOPN transferases among sequenced strains, consistent with attachment of MeOPN to different sugars in different CPS structures.…”
mentioning
confidence: 85%
“…C. jejuni contingency genes Cj1139, Cj1421, Cj1422 and Cj1426 are involved in capsule biosynthesis/ modification or LOS biosynthesis (Linton et al, 2000;McNally et al, 2007), and they experienced phase variation Chicken passage promotes C. jejuni mouse colonization to a non-functional protein or protein with modified function. So, phase variation could enhance colonization and disease by altering the ability of mice to mount an effective innate or adaptive immune response (Ang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%